Ageing passenger perceptions of ground access journeys to airports: A survey of UK residents. (March 2023) - Graham, Anne; Kruse, Willy; Budd, Lucy; Kremarik, Frances; Ison, Stephen
Abstract: In common with other developed nations, the UK population is ageing. This has impacts on all areas of economic and social activity, including transport and air travel. This paper aims to provide an initial assessment of the ground access journeys to UK airports made by ageing (65+ years) air travellers, a topic hitherto unexplored by the academic research community. Using data from two online surveys (each with 600 respondents) undertaken in 2020 of 1200 different ageing UK residents, this exploratory research reveals that the ease of undertaking the journey and comfort are key factors in determining ground access choice whilst environmental issues play a minimal role. Whilst this paper offers new insights into the ground access journeys of ageing air passengers, it also makes recommendations for future research that needs to be undertaken to further academic understandings of the needs and attitudes of this important, and growing, passenger segment. Highlights: The ground access journey is viewed more favourably than other air journey stages. Ease of undertaking the journey and comfort are key factors in ground access choice. Environmental issues play a minimal role in determining ground access choice. COVID-19 may encourage ageing passengers to use more cars and taxis.